Esterificação do ácido oleico e acetato de metila com zeólita WO3/USY: efeitos da impregnação do catalisador e modelagem cinética - Ketzer, Felipe (2020)
This work proposes the use of USY zeolite activated with tungsten oxide in the esterification of oleic acid with methyl acetate. Tunguistic acid was synthesized trought the acid treatment of sodium tungstate and was used as a precursor. The characterization of the catalysts showed that the general structure of the zeolite was maintained after impregnation. However, the acidity profile of WO3/USY zeolites has been highly altered, where the strong Brønsted acid sites of the original zeolite have been blocked by tungsten oxide, allowing the reagents to have been accessed to the new Lewis acid sites and hydrogen bonds. The change of adsorption mechanism favored the conversion of oleic acid to methyl oleate. The first-order reversible pseudo-homogeneous (PH) model was able to represent the experimental data catalyzed by the USY zeolite, since the heterogeneous models (ER and LH) were classified as overparameterized and were disregarded. Kinetic and thermodynamic modeling showed that the reaction is endothermic, with change in enthalpy of 59.83 kJ mol−1 and activation energy of 41.77 kJ mol−1. The proposal of a novel kinetic model considering the active sites of the WO3/USY catalyst shown a good fit to the experimental data of the reaction catalyzed by different catalysts. The Brønsted acidic sites of the USY zeolite and the weak acidic sites of the WO3/USY zeolite showed great importance in the esterification reaction. The zeolites activated by ultrasonic method showed the greatest conversions in methyl esters. The 10% WO3/USY US catalyst presented the best performance, converting 87% of oleic acid to methyl oleate after 3 hours of reaction, at 240 °C, with a ratio of oleic acid and methyl acetate of 1:10 and 10% (w/w) of catalyst. The use of WO3/USY zeolite shows a viable and effective catalyst to esterification of oleic acid with methyl acetate, which is in accordance to prospects of free-glycerol biodiesel production.